KINERJA PENGAWAS MADRASAH SE KABUPATEN OGAN KOMERING ULU TIMUR SUMATRA SELATAN - Hadi, Sopiyan (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2019)
of supervisory programs in each Madrasa which is categorized as accredited A, B, C and not accredited in Madrasah, Ogan Komering Ulu Timur Regency in 2017/2018. This research is a descriptive qualitative research. The results of this study indicate that the implementation of supervisor performance in Madrasah aliyah in Ogan Komering Ulu Timur can be categorized quite well. Supervision activities carried out by holding class visits and direct observation of the process of implementing learning in class. The supervisor has also provided recommendations and input to the teacher on strategies to overcome each problem, but the teacher does not always follow what is recommended by the supervisor. Work achievements achieved by supervisors in the field of research are still unsatisfactory. The role of supervisors is less dominant in efforts to improve school quality. Therefore, active participation and support from the government will be needed especially in efforts to improve the performance of supervisors, madrasa principals, teachers and employees.